Seasonal Air–Sea Exchange Dynamics of Polychlorinated Biphenyls Over the East China Marginal Seas: The Role of Water Masses in a Complex Coastal–Ocean Current System. Issue 15 (10th August 2022) - Yu, H. M.; Lin, T.; Guo, T. F.; Sun, X.; Cao, Y. B.; Duan, L.; Sun, X. S.; Guo, Z. G.
Abstract: Continental marginal seas are key reservoirs of anthropogenic pollutants. Understanding the physical processes controlling the air–sea exchange dynamics of polychlorinated biphenyls (PCBs) in the continental margin seas is crucial to constrain the contribution of PCBs from land and rivers to the ocean; however, the transport and fate of PCBs, and their controlling factors of air–sea exchange in the continental marginal seas still remain poorly understood. Here, we collected atmospheric and surface water samples from the Yellow Sea (YS) and East China Sea (ECS) in summer 2018 and winter 2019, and examined the PCB concentrations. The PCB air–sea gas exchange fluxes showed higher net volatilization in winter, largely due to southward movement of the strengthened Yellow Sea Coastal Current and Yangtze River Diluted Water with high PCB concentrations. Both the dissolved PCB concentrations in seawater and wind speed were the primary factors influencing the PCB air–sea exchange fluxes in winter. By contrast, weak PCB volatilization fluxes occurred when the Taiwan Warm Current with low PCB concentrations dominated in the ECS in summer. In comparison, the accumulation and release of some PCB homologues caused by a green tide in the coastal YS could lead to increased volatilization flux in summer. Our results suggest the transfer of air–sea exchange dynamics of PCBs from a water concentration‐dominated pattern to an environmental parameter‐controlled one due to their decreased land‐based input, and highlight the impact of water mass‐triggered changes (environmental parameters and algal blooms) on the air–sea exchange behavior of PCBs in the continental marginal sea. Plain Language Summary: Polychlorinated biphenyls (PCBs) are a kind of persistent organic pollutants, harmful to the physical health and marine ecology. Seawater acts as a reservoir for PCBs. PCBs in surface seawater could be released to the atmosphere. We found that ocean current greatly impacts the volatilization flux of PCBs from seawater to the atmosphere. The seasonal variation of ocean current in the East China Marginal Seas (ECMS) are complex. In winter, strong coastal currents and rivers brought a bulk of PCBs to the ECMS and contributed to a strong PCB volatilization flux; while in summer, clean ocean current dominated the ECMS and thus caused less PCB volatilization. The green tide could lead to a significant PCB volatilization due to degradation of microorganisms. This work highlights the importance of ocean currents and microorganism in seawater on the air–sea exchange dynamics of PCBs in the continental marginal sea. Key Points: Seasonal transport of ocean currents determined the dynamics of polychlorinated biphenyls (PCBs) air–sea exchange in the continental margin Environmental parameters are more important for the dynamics of PCB air–sea exchange over the remote sea areas than over the coastal waters Dechlorination process could lead to significant volatilization flux of tetra‐CB